2016
DOI: 10.7819/rbgn.v18i61.3058
|View full text |Cite
|
Sign up to set email alerts
|

The critical success factors for organizational performance of SMEs in Malaysia: a partial least squares approach

Abstract: Purpose -This paper seeks to examine the relationship between the determinants of organizational performance such as top management support, customer focus, employees' orientation, technology orientation, and entrepreneurial orientation in Malaysia.Design/methodology/approach -A quantitative research design was applied for this study. Data was collected through survey questionnaires applied to business owners and senior managers working in SMEs located in three Malaysian states, using purposive sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Research indicates that small businesses tend to have a higher failure rate as compared to large organisations, although they are commonly perceived as an engine of a country's economy (Bloch & Bhattacharya, 2016;Lo, Wang, Wah, & Ramayah, 2016). For example, in Malaysia, it was found that higher number of small and medium-sized enterprises (SMEs) indicated a worse performance in the first quarter of 2016 as compared to 2015 (SME Corp, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that small businesses tend to have a higher failure rate as compared to large organisations, although they are commonly perceived as an engine of a country's economy (Bloch & Bhattacharya, 2016;Lo, Wang, Wah, & Ramayah, 2016). For example, in Malaysia, it was found that higher number of small and medium-sized enterprises (SMEs) indicated a worse performance in the first quarter of 2016 as compared to 2015 (SME Corp, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Those companies that last over time do so because in one way or another, they are competitive in the market and their niche keeps them sustainable (Marín, 2015). However, it is important to create the competitive advantages that ensure their sustainability, and do not decline when there are periods of changes in the market (Lo, Wah, & Ramayah, 2016). According to Porter (2015), the competitive advantage is a characteristic that the company has, which differentiates it from its competitors, creating a unique offer where it allows the customers to prefer it, based on two main factors: differentiation (make products and services different from the competition) and the decrease in costs (have more efficient strategic actions than competitors).…”
Section: Organizational Competitivenessmentioning
confidence: 99%
“…In Least Developed Countries (LDCs) in Asia Micro and small enterprises account for 80% of the firms generating 80% employment and 40-70% of value added and in Bangladesh Micro and small enterprises account for the majority of firms (87%) providing 80% of total employment and contributing 15 percent to Gross Domestic Product (GDP) of the country (Narain, 2003). Women MSE's Business Survival Research indicates that Micro and Small Enterprises (MSE's) tend to have a lower survival rate as compared to large organizations, although they are commonly perceived as an engine of a country's economy (Bloch & Bhattacharya, 2016;Lo, Wang, Wah, &Ramayah, 2016). Many failure stories of MSE's reveal that their characteristics which include reactive, fire-fighting mentality, resource limitations, informal strategies, flexible structures, and lack of strategic planning processes may have contributed to their failures (Gnizy, Baker, & Grinstein, 2014).…”
Section: Concepts Of Entrepreneurshipmentioning
confidence: 99%
“…Research indicates that Micro and Small Enterprises (MSE's) tend to have a lower survival rate as compared to large organizations, although they are commonly perceived as an engine of a country's economy (Bloch & Bhattacharya, 2016;Lo, Wang, Wah, &Ramayah, 2016). Many failure stories of MSEs reveal that their characteristics which include reactive, fire-fighting mentality, resource limitations, informal strategies, flexible structures, and lack of strategic planning processes may have contributed to their failures (Gnizy, Baker, & Grinstein, 2014).…”
Section: Introductionmentioning
confidence: 99%